OPTIMALISASI PARENTING DALAM MEMBENTUK KARAKTER ANAK USIA DINI DI PAUD AISYIYAH 13 PEKANBARU - Siska Noviana (P3M STKIP 'Aisyiyah Riau, 2017)
The purpose of this study is to determine parenting activities in shaping early childhood character in Paud Aisyiyah 13 Pekanbaru, and to determine character education for early childhood in Paud Aisyiyah 13 Pekanbaru. The data collection research was carried out by conducting observations, interviews, and documentation, and this study used a qualitative descriptive method, namely explaining and presenting data from the results of the study, namely conducting direct research on parents, children, and teachers as samples in order to get a concrete picture of parenting activities. and character education for children. The method used in this research is descriptive method, by collecting data, compiling data, or classifying it, analyzing and interpreting it. The results showed that the parenting styles given by parents to their children have started well by teaching various kinds of responsibilities, and through good habituation to their children so that the children get used to it. Parents provide rules that are applied in the family such as tidying up play equipment after playing, and parents teaching independence to children even though they are not completely done by the children, but through these habits the children begin to get used to them. When holding parenting activities, time should be held that does not interfere with the child's parents' activities, so that they can attend activities held by school principals and teachers.